Dampak Budaya Kampus terhadap Keputusan Mahasiswa Memilih Tempat Kuliah - Siswanto, Iwan; Hasibuan, Lias; US, Kasful Anwar; Ridhwan, M. (STAI Auliaurrasyidin Tembilahan, 2021)
The purpose of this study was to determine the effect of campus culture on students' decisions to study at STAI Auliaurrasyidin Tembilahan. This study used a quantitative design by random sampling based on the proportions of Isaac and Michael with a significant level of 5% totaling 238 from a population of 748. Questionnaires were used to collect the data in this research and analyzed using simple regression analysis. The results showed that there was a significant cultural influence on student selection decisions. The results also showed that students’ organizations did not attract students' interest in making choices. Therefore, the campus should make culture a tool to make excellence and characteristics that can be used as promotional material to increase the number of students